2019
DOI: 10.1063/1.5099326
|View full text |Cite
|
Sign up to set email alerts
|

Plasma chemistry and dust-particle generation in pure methane plasma: Influence of the RF electrode cleanliness

Abstract: Hydrocarbon dust-particles are formed and grown to a large size (around 1 μm) in a low pressure capacitively coupled radio frequency discharge in methane. The methane decomposition leads to the formation of both spherical dust-particles in the plasma bulk and coating on the electrodes. Under ion bombardment, the coating on the biased top electrode peels off, leading to the fall of flakes. To better understand the role played by the electrode surface state on the plasma chemistry and on the dust-particle growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…A study of the sensitivity of the molecular growth kinetics to the boundary conditions adopted for the large molecular ions showed that even if these ions are assumed to be fully absorbed at the electrodes, they still insure a significant molecular growth and nucleation kinetics. In any case, the results obtained here are consistent with experimental studies showing that dust particle formation in hydrocarbon plasma may be very sensitive to the electrode surface and reactor wall conditioning [46]. This clearly emphasizes that an improved molecular growth and nucleation model should take into account a much more detailed surface model.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study of the sensitivity of the molecular growth kinetics to the boundary conditions adopted for the large molecular ions showed that even if these ions are assumed to be fully absorbed at the electrodes, they still insure a significant molecular growth and nucleation kinetics. In any case, the results obtained here are consistent with experimental studies showing that dust particle formation in hydrocarbon plasma may be very sensitive to the electrode surface and reactor wall conditioning [46]. This clearly emphasizes that an improved molecular growth and nucleation model should take into account a much more detailed surface model.…”
Section: Discussionsupporting
confidence: 89%
“…In any case, the results obtained here are consistent with experimental studies showing that dust particle formation in HC plasma may be very sensitive to the electrode surface and reactor wall conditioning. [46] This clearly emphasizes that an improved molecular growth and nucleation model should take into account a much more detailed surface model. In particular, the impact of sputtering and etching of the hydrogenated carbon films that form on the electrode in the HC containing plasmas on the composition of the gas phase should be included in the model.…”
Section: Sensitivity Of the Molecular Growth To The Assumption Made O...mentioning
confidence: 96%
“…In the experiment it was found that after thorough cleaning of the plasma chamber the etching process reached a stable output only after few treatment cycles, where an a-C:H layer formed atop the electrode accordingly. Similar findings of feedback from previous treatment cycles due to film deposition have also been reported for nanoparticle generation …”
Section: Resultssupporting
confidence: 83%
“…Similar findings of feedback from previous treatment cycles due to film deposition have also been reported for nanoparticle generation. 53 No additional treatment of the ZnO tetrapods to facilitate their nanostructuring has been performed previously to plasma etching. Thus, the formation of nanowire arrays by patterned preferential etching must be the result of the plasma etching process and pristine ZnO crystal properties only.…”
Section: Methodsmentioning
confidence: 99%
“…It can avoid the electrode participating in the CH 4 reforming reaction, which is beneficial to the PARM process. [ 197 , 198 , 199 , 200 ] Nevertheless, the relative abundance of the product species strongly depends on the discharge parameters of the RF reactor. The increase in the energy deposition in RF plasma torches leads to the formation of substantially more types of hydrocarbons, which is an urgent problem.…”
Section: Fundamentals Of Plasma‐assisted Reforming Of Methanementioning
confidence: 99%